Site Suitability Assessment for Neelambur Panchayat using GIS and AHP Techniques. Issue 1 (December 2020) - Navin Ganesh, V; Sachin, E; Ravikumar, R; Sanjay Kumar, S; Vijayakumar, S
Abstract: The rapid urbanization in the fast growing cities is posing a major problem for the planning authorities. Most of this urbanization is experienced in the peri-urban areas which refer to the settlements beyond, about or around cities. They are characterized by the changing economic and employment structure along with rapid population growth, changing spatial development patterns, unregulated growth, haphazard developments, low quality housing and inadequate infrastructure facilities. Proper site suitability assessment involving detailed investigation of the land parcels with respect to the available resources required for the urban settlements which will lead to sustainable growth of the peri-urban area is required. In the current research study, site suitability assessment has been carried out for Neelambur, one of the peri-urban areas of Coimbatore city. The factors considered for identifying the land parcels suitable for urban settlement included the land-use of the study area, proximity of sites to the nearest road, proximity of sites to the nearest facilities of importance and slope of the study area. The Analytical Hierarchy Process based Weighted Overlay Method was used in Geographic Information System to identify the land parcels suitable for urban settlements in order to ensure a sustainable development in the study area.The results indicated that 5.29 sq.km of the study area was classified as highly suitable for urban settlements. The results of the current study can be used by the local planning authorities in establishing development control norms for ensuring the sustainable growth of Neelambur.